AN ANALYSIS OF FACTORS INFLUENCING THE INTENTION TO PERFORM DIGITAL INFAQ AMONG THE PEOPLE OF BANJARMASIN - Rizky Maulana Dwiky Santosa (ADISAM Publisher, 2025)
This study aimed to examine the factors influencing the intention to perform digital infaq among residents of Banjarmasin. Using a quantitative approach, data were collected through questionnaires distributed to 100 respondents and analyzed using multiple linear regression. The research investigated the impact of eight independent variables: ZIS literacy, religiosity, perceived ease of use, trust, security, usefulness, transparency, and social influence on digital infaq intention. The findings revealed that only perceived ease of use and perceived usefulness had a significant positive effect on the intention to donate digitally. Other variables, including religiosity and trust, showed no statistically significant influence. Furthermore, the results of the simultaneous F-test indicated that the eight variables collectively did not significantly affect the intention to perform digital infaq. These results highlight the importance of user-centered design and practical benefits in promoting digital charitable behavior. The study suggests that digital infaq platforms must enhance usability and perceived value to effectively encourage participation, rather than relying solely on religious or social motivations